2019
DOI: 10.7150/thno.35343
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cancer therapy through synergetic photodynamic/immune checkpoint blockade mediated by a liposomal conjugate comprised of porphyrin and IDO inhibitor

Abstract: Cancer metastases is still a hurdle for good prognosis and live quality of breast cancer patients. Treatment strategies that can inhibit metastatic cancer while treating primary cancer are needed to improve the therapeutic effect of breast cancer.Methods: In this study, a dual functional drug conjugate comprised of protoporphyrin IX and NLG919, a potent indoleamine-2,3-dioxygenase (IDO) inhibitor, is designed to combine photodynamic therapy and immune checkpoint blockade to achieve both primary tumor and dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Investigation into the mechanisms behind the trigger for this anti-tumor immunity remains an interesting pursuit. Notably, recent studies have found that certain chemotherapies 38 , PTT 39 , photodynamic therapy 40 - 42 and other treatments 43 - 45 can initiate an antitumor immune response by inducing tumor cells to undergo immunogenic cell death (ICD). Furthermore, cancer cells undergoing ICD can release immunostimulatory damage-associated molecular patterns (DAMPs) that act as potent danger signals, including calreticulin (CRT) exposure on the surface of tumor cells, release of large amounts of high-mobility group box 1 (HMGB1) or extracellular secretion of adenosine triphosphate (ATP).…”
Section: Resultsmentioning
confidence: 99%
“…Investigation into the mechanisms behind the trigger for this anti-tumor immunity remains an interesting pursuit. Notably, recent studies have found that certain chemotherapies 38 , PTT 39 , photodynamic therapy 40 - 42 and other treatments 43 - 45 can initiate an antitumor immune response by inducing tumor cells to undergo immunogenic cell death (ICD). Furthermore, cancer cells undergoing ICD can release immunostimulatory damage-associated molecular patterns (DAMPs) that act as potent danger signals, including calreticulin (CRT) exposure on the surface of tumor cells, release of large amounts of high-mobility group box 1 (HMGB1) or extracellular secretion of adenosine triphosphate (ATP).…”
Section: Resultsmentioning
confidence: 99%
“…T cells were found to play an important role in tumor immunity [46] and inhibit the expression of IDO, which could reverse CD8 + T cell suppression in breast cancer cell-bearing mice [47]. Interfering with the activity of IDO could lead to strengthening the anti-tumor immune response by increasing the amount of CD8 + T lymphocyte in ltration [48]. In addition, the present data showed that combination treatment with oxaliplatin and D-MT increased the ratio of NK cells, which was also an important reason against tumor.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a nanoparticulate small-molecule inhibitor of PDL1 may be as effective as the antibody, which faces clinical translational issues with immunogenicity, high production costs, and limited tumor penetration. Additionally, Huang et al [40] co-loaded protoporphyrin IX with an IDO inhibitor into a liposome for delivery. In a murine model, they showed that their PDT system resulted in ICD, which stimulated an immune response as measured by an increase in CD8 T cell infiltration into the tumor as well as a reduction in distant tumor burden ( Figure 2c).…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…**, p < 0.01; ***, p < 0.001; #, Differences between two groups are statistically significant, #, p < 0.05; (b) Analysis of immunogenicity of GL261 and MCA205 cells treated with photodynamic therapy using photosen (PS) or photodithazine (PD) as a photosensitizer [37]. *, p < 0.006; (c) Infiltration of CD8 + T cells in 4T1 tumor-bearing mice after photodynamic treatment using PpIX and IDO inhibitor, NLG919 [40]. *, p < 0.05; ***, p < 0.001; (d) Analysis of in vivo immune response of photodynamic therapy co-delivered with melittin in mice bearing 4T1 tumors (reproduced with permission from ACS Nano, published by American Chemical Society) [42].…”
Section: Photodynamic Therapymentioning
confidence: 99%